Abemaciclib: safety and effectiveness of a unique cyclin-dependent kinase inhibitor. Issue 8 (2nd August 2020) - Gebbia, Vittorio; Valerio, Maria Rosaria; Firenze, Alberto; Vigneri, Paolo
ABSTRACT: Introduction: The discovery and the clinical availability of novel cyclin-dependent kinases 4 and 6 inhibitors have profoundly changed the therapeutic scenario of metastatic hormone receptor-positive breast carcinoma. Among these inhibitors, abemaciclib can induce potent and sustained cell cycle arrest and immune system stimulation. Areas covered: This review summarizes the safety profile and clinical efficacy data on abemaciclib alone or in combination with aromatase inhibitors or fulvestrant in metastatic hormone receptor-positive breast carcinoma. The management of patients treated with abemaciclib is the object of this paper. Expert opinion: As shown in phase 2 and 3 clinical trials on efficacy and tolerability, abemaciclib is a potentially convenient, safe, and effective agent for the treatment of patients with advanced hormone receptor-positive patients. Orally administered abemaciclib in combination with aromatase inhibitors or fulvestrant has the potential to allow significant improvement in survival outcomes, quality of life, response rate, and duration of response even in poor prognosis subgroups. Adequate patients' information, clinical selection, and prompt, proactive management of side effects are mandatory.